Association between dietary patterns and chronic kidney disease in a middle-aged Chinese population. Issue 6 (2nd April 2020) - Xu, Shan-Shan; Hua, Jun; Huang, Yi-Qian; Shu, Long
Abstract: Objective: To explore the relationship between dietary patterns and risk of chronic kidney disease (CKD) in Chinese adults aged 45–59 years. Design: Dietary data were collected using a semi-quantitative FFQ. Factor analysis was used to identify the major dietary patterns. Logistic regression models were applied to clarify the association between dietary patterns and the risk of CKD. Setting: The present study population was a part of the population-based Nutrition and Health Study performed in the city of Hangzhou, Zhejiang Province, eastern China. Participants: A total of 2437 eligible participants (45–59 years) were enrolled in the present cross-sectional study from June 2015 to December 2016. Results: Three major dietary patterns were identified: 'traditional southern Chinese', 'Western' and 'grains–vegetables' patterns, collectively accounting for 25·6 % of variance in the diet. After adjustment for potential confounders, participants in the highest quartile of the Western pattern had greater odds for CKD (OR = 1·83, 95 % CI 1·21, 2·81; P < 0·05) than those in the lowest quartile. Compared with the lowest quartile of the grains–vegetables pattern, the highest quartile had lower odds for CKD (OR = 0·84, 95 % CI 0·77, 0·93; P < 0·05). In addition, there was no significant association between the traditional southern Chinese pattern and risk of CKD ( P > 0·05). Conclusions: Our results suggest that the Western pattern is associated with an increased risk, whereas the grains–vegetables pattern is associated with a reduced risk for CKD. These findings can guide dietary interventions for the prevention of CKD in a middle-aged Chinese population.